Introduction to grayscale calibration and related aspects of medical imaging grade liquid crystal displays. - Fetterly KA; Blume HR; Flynn MJ; Samei E (Journal of Digital Imaging, 2008)
Consistent presentation of digital radiographic images at all locations within a medical center can help ensure a high level of patient care. Currently, liquid crystal displays (LCDs) are the electronic display technology of choice for viewing medical images. As the inherent luminance (and thereby perceived contrast) properties of different LCDs can vary substantially, calibration of the luminance response of these displays is required to ensure that observer perception of an image is consistent on all displays. The digital imaging and communication in medicine (DICOM) grayscale standard display function (GSDF) defines the luminance response of a display such that an observer's perception of image contrast is consistent throughout the pixel value range of a displayed image. The main purpose of this work is to review the theoretical and practical aspects of calibration of LCDs to the GSDF. Included herein is a review of LCD technology, principles of calibration, and other practical aspects related to calibration and observer perception of images presented on LCDs. Both grayscale and color displays are considered, and the influence of ambient light on calibration and perception is discussed.